To <span>transform the quadratic equation into the equation form (x + p)2 = q we shall proceed as follows:
3+x-3x^2=9
putting like terms together we have:
-3x^2+x=6
dividing through by -3 we get:
x^2-x/3=-2
but
c=(b/2a)^2
c=(-1/6)^2=1/36
thus the expression will be:
x^2-x/3+1/36=-2+1/36
1/36(6x-1)</span>²=-71/36
the answer is:
1/36(6x-1)²=-71/36
800 is 10 times as much as 80
Ans: About 2.30
-15 x 3.16 / 9 = x sqrt
-15 x 3.16 = - 47.4
-47.4 / 9 = -5.27
-5.27 sqrt = About 2.30
Hope this helped :)
Since both equations equal Y, set them equal to each other and solve.
3x -1 = -2x +9
Add 2x to each side:
5x - 1 = 9
Add 1 to each side:
5x = 10
Divide both sides by 5:
x = 10/5
x = 2
Now replace x with 2 and solve for y:
y = 3(2) -1 = 6-1 = 5
x = 2, y = 5 (2,5)